2014
DOI: 10.1002/ejsp.2059
|View full text |Cite
|
Sign up to set email alerts
|

Reflective minds and open hearts: Cognitive style and personality predict religiosity and spiritual thinking in a community sample

Abstract: Corrigendum: Reflective minds and open hearts: Cognitive style and personality predict religiosity and spiritual thinking in a community sample After online and print publication of the study of Browne, Pennycook, Goodwin, and McHenry (2014), an error was detected in the abstract of the article. In the second sentence of the abstract, 'higher' should be corrected to 'lower' so the sentence should read: 'In a relatively large (N = 1093), older community sample (M = 55.4 years), analytic cognitive style was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 46 publications
(89 reference statements)
3
22
0
3
Order By: Relevance
“…Conclusively, however, results do suggest that analytic thinking predicts vaccine endorsement in the US (see Figure 3), both singularly and holding constant demographic, political, and related psychological variables. This finding is not surprising: it is certainly in line with research linking a willingness and ability to think analytically with higher likelihood of acceptance of mainstream scientific ideas, such as the theory of evolution (see Gervais, 2015), while linking low willingness/ability to think analytically with belief in the paranormal, religious, and other nonscientific beliefs (Browne et al, 2014;Pennycook et al, 2012). That is,…”
Section: Implications: Cognitive Style Vaccine Endorsement and Affesupporting
confidence: 75%
See 1 more Smart Citation
“…Conclusively, however, results do suggest that analytic thinking predicts vaccine endorsement in the US (see Figure 3), both singularly and holding constant demographic, political, and related psychological variables. This finding is not surprising: it is certainly in line with research linking a willingness and ability to think analytically with higher likelihood of acceptance of mainstream scientific ideas, such as the theory of evolution (see Gervais, 2015), while linking low willingness/ability to think analytically with belief in the paranormal, religious, and other nonscientific beliefs (Browne et al, 2014;Pennycook et al, 2012). That is,…”
Section: Implications: Cognitive Style Vaccine Endorsement and Affesupporting
confidence: 75%
“…Although this seems a simple exercise in equating 'like with like', the literature supports this conjecture at least at the level of predictor and outcome-type: an analytic cognitive style has been positively associated not just with higher education level, but with an overall higher level of acceptance of scientifically founded beliefs, and concurrent lower levels of belief in pseudoscience; supernatural phenomena; the paranormal, and belief in conspiracy theories (Aarnio & Lindeman, 2005;Browne, Pennycook, Goodwin, & McHenry, 2014;Genovese, 2005;Gervais & Norenzayan, 2012;Gervais, 2015;Pennycook, Cheyne, Seli, Koehler, & Fugelsang, 2012;Swami, Voracek, Stieger, Tran, & Furnham, 2014). For instance, greater endorsement of evolution, a foundational scientific principle, along with rejection of creationism, was recently found by Gervais (2015) to be predicted by higher levels of analytical thinking, while Gervais and Norenzayan 2012, along with (Browne et al, 2014) observed higher scores on measures of analytical thinking associated with lower religiosity and spirituality. Further, Aarnio and Lindeman (2005) found that analytic thinking mediated a negative relationships between education level and belief in the paranormal among Finnish university students, while increases in analytical thinking were found associated with lowered propensity to believe conspiracy theories in Swami et al 2014-which presumably equates to a greater acceptance of more mainline, scientifically founded beliefs (see Kata, 2012 -more on conspiracy theories will follow).…”
Section: Minimal Research On Analytic Thinking and Vaccine Endorsementmentioning
confidence: 98%
“…Desde esta perspectiva, distintos estudios han encontrado relaciones entre los constructos numinosos y el FFM en diferentes países como Australia (Browne, Pennycook, Goodwin, & McHenry, 2014), Austria (Schnell, 2012), Bélgica (Duriez & Soenens, 2006;Duriez, Soenens, & Beyers, 2004;Saroglou & Fiasse, 2003), Canadá (Browne et al, 2014;Taylor & MacDonald, 1999), España (Saroglou & Muñoz García, 2008), Eslovaquia (Gajdosova, Orosova, Janovska, & Benka, 2014;Halama, Martos, & Adamovová, 2010), Estados Unidos (Henningsgaard & Arnau, 2008;Rowatt & Kirkpatrick, 2002), Hungría (Halama et al, 2010), Irán (Aghababaei, 2013;Aguilar-Vafaie & Moghanloo, 2008;Mirsaleh, Rezai, Kivi, & Ghorbani, 2010;Salmanpour & Issazadegan, 2012), Inglaterra (Lewis, 1999), Noruega (Kaldestad, 1996) o Turquía (Dirilen-Gümüş, 2010), en diferentes religiones (Aghababaei, 2013;Aguilar-Vafaie & Moghanloo, 2008) y grupos etarios (Taylor & MacDonald, 1999).…”
Section: El Modelo De Los Cinco Factoresunclassified
“…Por su parte, si bien en numerosos estudios la relación entre la religiosidad y la apertura también puede parecer positiva, si se controla la espiritualidad, esta tiende a resultar negativa (Browne et al, 2014;McCullough & Willoughby, 2009;Saroglou, 2002).…”
Section: El Modelo De Los Cinco Factoresunclassified
“…After online and print publication of the study of Browne, Pennycook, Goodwin, and McHenry (), an error was detected in the abstract of the article. In the second sentence of the abstract, ‘higher’ should be corrected to ‘lower’ so the sentence should read:
‘ In a relatively large (N = 1093), older community sample (M = 55.4 years), analytic cognitive style was associated with a lower probability of affiliating with a religious denomination and a lower probability of possessing strong religious faith ’.
…”
mentioning
confidence: 99%